Розробка веб-системи інтернет-магазину «shop on wheels» - Жуков, В. Є. (ХНУРЕ, 2020)
One of the urgent tasks of each online service is the delivery of purchased products to the customer. In large stores, a special unit is responsible for this question. What solutions are possible for a small company? The best choice will be the service of a professional courier service. Even with a small number of orders, such delivery can not only promptly bring the purchased goods to the buyer, but also offer favorable rates and conditions for cooperation.